2002
DOI: 10.1097/00000433-200209000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Suicide by Self-Immolation in Durban, South Africa

Abstract: Self-immolation is an uncommon method of suicide, and its occurrence in South Africa is thus far unknown. This study aimed to determine the prevalence of self-immolation deaths and to establish a profile of these cases and the circumstances under which this condition occurs. A 5-year (1996-2000) retrospective review at a mortuary in Durban, South Africa, was conducted. Data were obtained from the Department of Forensic Medicine, the Medical Research Council's National Injury Mortality Surveillance System, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2004
2004
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 13 publications
4
26
0
1
Order By: Relevance
“…In Durban (South Africa), 9.9% of all suicides were the result of selfsacrifice 12 . On the other hand, in Germany, burn was much less used as a means of suicide, accounting for only 0.76% of all suicides in Berlin 13 .…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…In Durban (South Africa), 9.9% of all suicides were the result of selfsacrifice 12 . On the other hand, in Germany, burn was much less used as a means of suicide, accounting for only 0.76% of all suicides in Berlin 13 .…”
Section: Results Results Results Resultsmentioning
confidence: 99%
“…Studies of specific causes have reported gender differences with women overrepresented among burns due to kerosene stove explosions [27] and men among petrol fire disaster victims [28]. Studies also show that South African men are a particular risk group for burns related to interpersonal violence [19,29,30] and women, for self-inflicted burns [19,29,31]. There are also indications that there might be an over-representation of burns among women during the weekend [8].…”
Section: Introductionmentioning
confidence: 99%
“…As stated earlier, self-immolation appears to be more common in those regions of the world. Higher rates by these same racial and ethnic groups may also been seen in immigrant populations [6,[14][15][16][17]]. There appears to be a higher rate of self-immolation committed by immigrants in England and South Africa, compared to the non-immigrant population.…”
Section: Low-income Countries/ Africa -Eastern Countriesmentioning
confidence: 98%
“…Home is the main location for immolation, described in 50 to 65% of the cases [8,17,28,29,[31][32][33]38]. Some psychopathological characteristics may influence this choice of location.…”
Section: Locationmentioning
confidence: 99%
See 1 more Smart Citation